Skeletal Colonization by Breast Cancer Cells Is Stimulated by an Osteoblast and β2AR-Dependent Neo-Angiogenic Switch - Mulcrone, Patrick L.; Campbell, J Preston; Clément-Demange, Lise; Anbinder, Ana Lia [UNESP]; Merkel, Alyssa R.; Brekken, Rolf A.; Sterling, Julie A.; Elefteriou, Florent (Oxford University Press (OUP), 2017)
The skeleton is a common site for breast cancer metastasis. Although significant progress has been made to manage osteolytic bone lesions, the mechanisms driving the early steps of the bone metastatic process are still not sufficiently understood to design efficacious strategies needed to inhibit this process and offer preventative therapeutic options. Progression and recurrence of breast cancer, as well as reduced survival of patients with breast cancer, are associated with chronic stress, a condition known to stimulate sympathetic nerve outflow. In this study, we show that stimulation of the beta 2-adrenergic receptor (β2AR) by isoproterenol, used as a pharmacological surrogate of sympathetic nerve activation, led to increased blood vessel density and Vegf-a expression in bone. It also raised levels of secreted Vegf-a in osteoblast cultures, and accordingly, the conditioned media from isoproterenol-treated osteoblast cultures promoted new vessel formation in two ex vivo models of angiogenesis. Blocking the interaction between Vegf-a and its receptor, Vegfr2, blunted the increase in vessel density induced by isoproterenol. Genetic loss of the β2AR globally, or specifically in type 1 collagen-expressing osteoblasts, diminished the increase in Vegf-positive osteoblast number and bone vessel density induced by isoproterenol, and reduced the higher incidence of bone metastatic lesions induced by isoproterenol after intracardiac injection of an osteotropic variant of MDA-MB-231 breast cancer cells. Inhibition of the interaction between Vegf-a and Vegfr2 with the blocking antibody mcr84 also prevented the increase in bone vascular density and bone metastasis triggered by isoproterenol. Together, these results indicate that stimulation of the β2AR in osteoblasts triggers a Vegf-dependent neo-angiogenic switch that promotes bone vascular density and the colonization of the bone microenvironment by metastatic breast cancer cells. © 2017 American Society for Bone and Mineral Research.
Keywords: BONE VASCULATURE; BREAST CANCER; OSTEOBLAST; VEGF; β2AR